2018
DOI: 10.1021/acsami.8b10521
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Nanocarrier-Mediated Codelivery of Simvastatin and Noggin siRNA for Synergistic Enhancement of Osteogenesis

Abstract: The inexpensive hypolipidemic drug simvastatin (SIM), which promotes bone regeneration by enhancing bone morphogenetic protein 2 (BMP-2) expression, has been regarded as an ideal alternative to BMP-2 therapy. However, SIM has low bioavailability and may induce the upregulation of the BMP-2-antagonistic noggin protein, which greatly limits the osteogenic effect. Here, a pH-sensitive copolymer, monomethoxy-poly(ethylene glycol)- b-branched polyethyleneimine- b-poly( N-( N', N'-diisopropylaminoethyl)- co-benzylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…At pH 7.4, the nanoplex of N/P 10 showed roughly spherical shape and fairly uniform size of about 155.0 ± 10.8 nm in diameter (Figure D), which was slightly smaller than that detected by DLS measurement. On the contrary, random polymeric aggregates were observed at pH 5.0 (Figure E), which had a particle size of 1088 ± 108.5 nm as detected by the DLS measurement (Table S3, Supporting Information), likely because the complete protonation of DIP caused a hydrophilic transition of the PAsp(DIP–BzA) block, which induced the disassembly of nanoplex . As shown in Figure S3 (Supporting Information), the fluorescent intensity of Cy3‐labeled miRNA increased via pH 5.0 preincubation as compared with pH 7.4, which indicated that Cy3‐labeled miRNA was released from T‐SCR/S nanoplex due to the disassembly of T‐SCR nanoplex at pH 5.0 lowering miRNA complexation ability of free VA–PEG–bPEI–PAsp(DIP–BzA) during endo‐lysosomal escape .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…At pH 7.4, the nanoplex of N/P 10 showed roughly spherical shape and fairly uniform size of about 155.0 ± 10.8 nm in diameter (Figure D), which was slightly smaller than that detected by DLS measurement. On the contrary, random polymeric aggregates were observed at pH 5.0 (Figure E), which had a particle size of 1088 ± 108.5 nm as detected by the DLS measurement (Table S3, Supporting Information), likely because the complete protonation of DIP caused a hydrophilic transition of the PAsp(DIP–BzA) block, which induced the disassembly of nanoplex . As shown in Figure S3 (Supporting Information), the fluorescent intensity of Cy3‐labeled miRNA increased via pH 5.0 preincubation as compared with pH 7.4, which indicated that Cy3‐labeled miRNA was released from T‐SCR/S nanoplex due to the disassembly of T‐SCR nanoplex at pH 5.0 lowering miRNA complexation ability of free VA–PEG–bPEI–PAsp(DIP–BzA) during endo‐lysosomal escape .…”
Section: Resultsmentioning
confidence: 91%
“…The VA‐terminated pH‐sensitive copolymer, VA–PEG–bPEI–PAsp(DIP–BzA) or T‐PBP, was synthesized according to our recent report ( Figure A; Figure S1, Supporting Information) and characterized by gel permeation chromatography (GPC) and 1 H NMR. GPC chromatograms showed a unimodal molecular weight distribution for all copolymers and an increase in the molecular weight of final copolymer compared with the prepolymer, suggesting that VA‐terminated PEG was conjugated to final copolymer (Figure S2 and Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined therapy involving codelivery of two or more drugs is a common tumor treatment strategy (19)(20)(21)(22), but codelivery of Cas9 with small-molecular drugs has not been investigated thoroughly. For controlled release of Cas9, one approach is to induce release using a combination of internal and external stimuli (23).…”
Section: Introductionmentioning
confidence: 99%